Esports between the Sports and Entertainment Industry: In Search of Division Lines - Gábriš Tomáš; Hamuľák Ondrej; Kocharyan Hovsep; Ramil Pablo Martínez (TalTech Journal of European Studies)
The growing popularity and expansion of esports have prompted an academic and legal debate, where its classification as either a sport or a form of entertainment remains unclear. This article explores the dual nature of esports, providing an overview of the legal and regulatory challenges it presents. It opens the discussion by addressing the space occupied by esports, distinguishing it from the traditional understanding of analogue sports while introducing the role of various stakeholders. The article then delves into the legal discussion taking place at the EU level, exploring also how the national legal reality of some Member States approach esports. The study highlights the urgency of finding a balanced approach that recognises esports as a hybrid entity, necessitating a regulatory model that draws from both sports law and entertainment law. Furthermore, the article complements the analysis by addressing emerging normative systems within esports, including autonomous governance structures and the potential need for state intervention to address issues such as doping, match-fixing, and the protection of minors. By analysing the existing legal frameworks in non-EU countries, particularly in Asia and North America, the authors suggest that esports needs to be approached as a new type of sport—a perspective that should be reflected in future EU regulations.